Improving carrier mobility in two-dimensional semiconductors with rippled materials - Ng, Hong Kuan (2023)
Two-dimensional (2D) semiconductors could potentially replace silicon in future electronic devices. However, the low carrier mobility in 2D semiconductors at room temperature, caused by strong phonon scattering, remains a critical challenge. Here we show that lattice distortions can reduce electron–phonon scattering in 2D materials and thus improve the charge carrier mobility. We introduce lattice distortions into 2D molybdenum disulfide (MoS2) using bulged substrates, which create ripples in the 2D material leading to a change in the dielectric constant and a suppressed phonon scattering. A two orders of magnitude enhancement in room-temperature mobility is observed in rippled MoS2, reaching ∼900 cm2 V−1 s−1, which exceeds the predicted phonon-limited mobility of flat MoS2 of 200–410 cm2 V−1 s−1. We show that our approach can be used to create high-performance room-temperature field-effect transistors and thermoelectric devices.